The Risk Ratio of Immune-Related Colitis, Hepatitis, and Pancreatitis in Patients With Solid Tumors Caused by PD-1/PD-L1 Inhibitors: A Systematic Review and Meta-Analysis - Tian, Yuan; Zhang, Zewen; Yang, Xiaowei; Li, Donghua; Zhang, Li; Li, Zhuoqi; Zhang, Shuisheng; Mao, Yantao; Jin, Chenxing; Zhao, Yi (Frontiers in Oncology, 2020)
None.The meta-analysis was put into practice in evaluating the risk ratio of immune-related digestive system inflammation in patients with solid tumors caused by PD-1/PD-L1 inhibitors.The process of the meta-analysis was performed by us according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines.After screening and eligibility assessment, a total of 26 clinical trials involving 16409 patients were selected for the final quantitative synthesis. Immune-related digestive system inflammations, the Nivolumab group was significantly lower than that of the control group. Similar analysis results could also be seen in the incidence risk of hepatitis. We did not find a statistically significant effect on the incidence of immune-related pancreatitis after the use of PD-1/PD-L1 inhibitors.The use of PD-1/PD-L1 inhibitors increased the incidence risk of immune-related colitis and hepatitis, but this potential to increase the incidence risk of the disease was weaker than Ipilimumab.